2012
DOI: 10.1002/cbf.2897
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and apoptotic effects of chalcone derivatives of 2‐acetyl thiophene on human colon adenocarcinoma cells

Abstract: Recent studies report that chalcones exhibit cytotoxicity to human cancer cell lines. Typically, the form of cell death induced by these compounds is apoptosis. In the context of the discovery of new anticancer agents and in light of the antitumour potential of several chalcone derivatives, in the present study, we synthesized and tested the cytotoxicity of six chalcone derivatives on human colon adenocarcinoma cells. Six derivatives of 3-phenyl-1-(thiophen-2-yl) prop-2-en-1-one were prepared and characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 36 publications
1
19
0
Order By: Relevance
“…Some chalcones displayed marked antiproliferative effects, via apoptosis and autophagy induction (32) others enhance TRAILinduced apoptosis (37) or ROS production (38) etc. Numerous chalcones derivate mentioned in the previous section induced apoptosis via inner mitochondrial pathway through overexpression of Bax protein and active caspase-3 (28,34,35). Our results indicated that chalcone analog treatment of HCT-116 cells caused overexpression of active, mitochondrial pro-apoptotic Bax protein and active caspase-3 compared to the control cells.…”
Section: Discussionsupporting
confidence: 50%
“…Some chalcones displayed marked antiproliferative effects, via apoptosis and autophagy induction (32) others enhance TRAILinduced apoptosis (37) or ROS production (38) etc. Numerous chalcones derivate mentioned in the previous section induced apoptosis via inner mitochondrial pathway through overexpression of Bax protein and active caspase-3 (28,34,35). Our results indicated that chalcone analog treatment of HCT-116 cells caused overexpression of active, mitochondrial pro-apoptotic Bax protein and active caspase-3 compared to the control cells.…”
Section: Discussionsupporting
confidence: 50%
“…Morever thiophene containing chalcones ( Figure 1) were reported in various studies that it have bioactive potential such as antibacterial, apoptotic, anti-angiogenic and radical scavenging agent (11)(12)(13)(14)(15). On the other hand, there is no study on the antifungal and anti-biofilm activities of the 1,3di(thiophen-2-yl)prop-2-en-1-one (4) according to our literature survey.…”
Section: Introductionmentioning
confidence: 88%
“…2). We anticipated that due to the well known bioisosterism of thiophene ring with benzene the newly designed molecules (B) would retain the PDE4 inhibitory properties of A. Additionally, in view of the fact that the thiophene ring being integral part of several anticancer agents/drugs [7,8] as well as cytotoxic/apoptotic agents [9] we expected potential apoptosis inducing properties of B.…”
Section: Introductionmentioning
confidence: 98%